The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.3727/096368912x658683
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of Serotonin Transporters with 4-[18F]-ADAM in a Parkinsonian Rat Model

Abstract: This study was undertaken to address the effects of fetal mesencephalic tissue transplantation on the serotonin system in a rat model of Parkinson's disease (PD) while also investigating the usefulness of 4-[18 F]-ADAM (a serotonin transporter imaging agent) coupled with micro-PET for imaging serotonin transporters (SERTs). A PD model was induced by unilateral injection of 6-hydroxydopamine (6-OHDA) into the right medial forebrain bundle of the nigrostriatal pathway, while cell transplantation was performed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…In the rat striatum, DAT concentration is several folds higher than the concentration of SERT, and in normal healthy rat, striatal tissue binding of [ 123 I]β-CIT can be considered to be mediated mainly by DAT [30]. Even though SERT binding activity is decreased in the rat 6-OHDA model [32], there may still be a change in the proportion of striatal DAT versus SERT binding of [ 123 I]β-CIT. In a recent PET study, Sossi et al [33] observed changes in the non-specific background signal from [ 11 C]-methylphenidate (DAT tracer) in the striatum of unilaterally 6-OHDA-lesioned rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat striatum, DAT concentration is several folds higher than the concentration of SERT, and in normal healthy rat, striatal tissue binding of [ 123 I]β-CIT can be considered to be mediated mainly by DAT [30]. Even though SERT binding activity is decreased in the rat 6-OHDA model [32], there may still be a change in the proportion of striatal DAT versus SERT binding of [ 123 I]β-CIT. In a recent PET study, Sossi et al [33] observed changes in the non-specific background signal from [ 11 C]-methylphenidate (DAT tracer) in the striatum of unilaterally 6-OHDA-lesioned rats.…”
Section: Discussionmentioning
confidence: 99%
“…Of 24 Parkinsonian rats (PD group) initially scanned by PET, six received a graft consisting of ventral mesencephalic tissue (2 µl) and HBSS (2 µl; VM group), six received a graft consisting of mesencephalic tissue (2 µl) and OECs (2 µl; 2 × 10 5 cells; VM–OECs group), and six received a graft consisting of OECs (2 µl; 2 × 10 5 cells; OECs group). The mesencephalic tissue was dissected from embryonic day 14 (E14) fetal brains (Takeuchi et al ., ), with the dissection area selected according to the protocols of Dunnet and Björklund (Dunnett and Björklund, ) with minor modifications (Weng et al ., ). The dissected tissue blocks contained the ventral mesencephalon and part of the ventral pontine raphe, which contain dopaminergic and serotonergic cell bodies, respectively.…”
Section: Methodsmentioning
confidence: 97%
“…Considering the partial volume effect between brain regions on voxel‐based PET images (Lehnert et al ., ), the VOIs were bordering within the brain structures. The SUR was expressed as (striatum ‐ cerebellum) / cerebellum, the cerebellum was defined as reference region (Ma et al ., ; Li et al ., ; Weng et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations